NusG, an Ancient Yet Rapidly Evolving Transcription Factor - Wang, Bing; Artsimovitch, Irina (Frontiers in Microbiology, 2021)
Timely and accurate RNA synthesis depends on accessory proteins that instruct RNA polymerase (RNAP) where and when to start and stop transcription. Among thousands of transcription factors, NusG/Spt5 stand out as the only universally conserved family of regulators. These proteins interact with RNAP to promote uninterrupted RNA synthesis and with diverse cellular partners to couple transcription to RNA processing, modification or translation, or to trigger premature termination of aberrant transcription. NusG homologs are present in all cells that utilize bacterial-type RNAP, from endosymbionts to plants, underscoring their ancient and essential function. Yet, in stark contrast to other core RNAP components, NusG family is actively evolving: horizontal gene transfer and sub-functionalization drive emergence of NusG paralogs, such as bacterial LoaP, RfaH, and UpxY. These specialized regulators activate a few (or just one) operons required for expression of antibiotics, capsules, secretion systems, toxins, and other niche-specific macromolecules. Despite their common origin and binding site on the RNAP, NusG homologs differ in their target selection, interacting partners and effects on RNA synthesis. Even among housekeeping NusGs from diverse bacteria, some factors promote pause-free transcription while others slow the RNAP down. Here, we discuss structure, function, and evolution of NusG proteins, focusing on unique mechanisms that determine their effects on gene expression and enable bacterial adaptation to diverse ecological niches.